(untitled) (Journal of Mechanical Engineering, 2009)
In this paper, the design and construction of a cascade impactor for reducing particulate emission from a diesel engine exhaust has been presented and experiments have been carried out to determine its collection efficiency. The cascade impactor designed in this work consists of four stages having successive decreasing nozzle diameter so as to capture successive smaller diameter particles in the stages. The successive nozzle diameters (D) were selected 2.1cm, 1.7cm, 1.3cm and 0.9cm. Also the distances between nozzle and impaction plate (S) were taken as 2.1cm, 1.4cm, 0.9cm and 0.45cm respectively so that S/D for succeeding stages becomes 1, 0.82, 0.7 and 0.5 respectively. In this investigation, collection efficiency of the cascade impactor based on different engine operating conditions has been determined. Effect of fitting the cascade impactor to engine exhaust on different engine parameters and engine emissions were also found out. At a constant speed of 1000 rpm, a maximum collection efficiency of about 85% of the impactor was obtained at a load of 6kg. A slight decrease in brake thermal efficiency of the engine with the cascade impactor was also noticed. However, by fitting the cascade impactor to the engine, CO and NOx emissions were found to decrease. Keywords: Real impactor, cascade impactor, Reynolds number, Stokes number, collection efficiency. doi:10.3329/jme.v39i1.1830 Journal of Mechanical Engineering, vol. ME39, No. 1, June 2008 26-29